Evaluation of Maxillary Posterior Teeth Proximity to the Adjacent Sinuses in a Turkish Subpopulation: Implications for Dental Education and Clinical Practice - Yiğit, Damla; Dolaşir, Gizem; Çelik, Sabri; Sessiz, Rüya; Alan, Raif (UI Scholars Hub, 2025)
Objectives: This study aimed to evaluate the proximity of upper posterior tooth roots to adjacent sinus borders using cone-beam computed tomography (CBCT) in a Turkish subpopulation and to assess dental students’ competence in identifying this anatomical relationship. Methods: CBCT scans of 171 patients were analyzed. The vertical relationship between premolars and molar roots, and the maxillary sinus (MS) border was categorized into four types (Type 0–3). Interrater agreement between three final-year dental students and an experienced radiologist was measured. Results: Type 0 was the most frequent classification, except for first molars, where Type 2 and Type 3 predominated. MS-root distances were significantly greater in men for specific teeth. Interrater agreement between the radiologist and each student was substantial. Conclusion: The relationship between the MS and posterior teeth varies by tooth type, gender, and age. Second molars most frequently lie closest to the MS, increasing the likelihood of sinus-related complications. Dental students demonstrated substantial diagnostic agreement with the radiologist, highlighting the value of structured radiographic education. These findings underscore the need for thorough radiographic assessment to minimize procedural risks in clinical practice.